Post-revisionism: Conflict (Ir)resolution and the Limits of Ambivalence in Kevin McCarthy’s Peeler - McAteer, Michael (Text Matters: A Journal of Literature, Theory and Culture, 2018)
This essay considers a historical novel of recent times in revisionist terms, Kevin McCarthy’s debut novel of 2010, Peeler. In doing so, I also address the limitations that the novel exposes within Irish revisionism. I propose that McCarthy’s novel should be regarded more properly as a post-revisionist work of literature. A piece of detective fiction that is set during the Irish War of Independence from 1919 to 1921, Peeler challenges the romantic nationalist understanding of the War as one of heroic struggle by focusing its attention on a Catholic member of the Royal Irish Constabulary. In considering the circumstances in which Sergeant Seán O’Keefe finds himself as a policeman serving a community within which support for the IRA campaign against British rule is strong, the novel sheds sympathetic light on the experience of Catholic men who were members of the Royal Irish Constabulary until the force was eventually disbanded in 1922. At the same time, it demonstrates that the ambivalence in Sergeant O’Keefe’s attitudes ultimately proves unsustainable, thereby challenging the value that Irish revisionism has laid upon the ambivalent nature of political and cultural circumstances in Ireland with regard to Irish-British relations. In the process, I draw attention to important connections that McCarthy’s Peeler carries to Elizabeth Bowen’s celebrated novel of life in Anglo-Irish society in County Cork during the period of the Irish War of Independence: The Last September of 1929.